Biomass burning organic aerosols significantly influence the light absorption properties of polarity-dependent organic compounds in the Pearl River Delta Region, China. (November 2020) - Jiang, Hongxing; Li, Jun; Chen, Duohong; Tang, Jiao; Cheng, Zhineng; Mo, Yangzhi; Su, Tao; Tian, Chongguo; Jiang, Bing; Liao, Yuhong; Zhang, Gan
Highlights: The main BrC fraction in WSOC and WISOC were HULIS and middle-polar fraction. The non-fossil carbon was enriched in high polar carbon fractions Oxidized BBOA are the major BrC in HULIS and MP, while primary BBOA are mainly in LP. More Nitrogen-containing compounds from BB increase the BrC absorption in PRD winter. Abstract: Atmospheric brown carbon (BrC) is an important constituent of light-absorbing organic aerosols with many unclear issues. Here, the light-absorption properties of BrC with different polarity characteristics at a regional site of Pearl River Delta Region during 2016–2017, influenced by sources and molecular compositions, were revealed using radiocarbon analysis and Fourier transform ion cyclotron resonance mass spectrometry. Humic-like substance (HULIS), middle polar (MP), and low polar (LP) carbon fractions constitute 46 ± 17%, 30 ± 7%, and 7 ± 3% of total absorption coefficient from bulk extracts, respectively. Our results show that the absorption proportions of HULIS and MP to the total BrC absorption are higher than their mass proportions to organic carbon mass, indicating that HULIS and MP are the main light-absorbing components in water-soluble and water-insoluble organic carbon fractions, respectively. With decreases in non-fossil HULIS, MP, and LP carbon fractions (66 ± 2%, 52 ± 2%, and 36 ± 3%, respectively), the abundances of unsaturated compounds and mass absorption efficiency at 365 nm of three fractions decreased synchronously. Increases in both non-fossil carbon and levoglucosan in winter imply that the enhanced light-absorption could be attributed to elevated levels of biomass burning organic aerosols (BBOA), which increases the number of light-absorbing nitrogen-containing compounds. Moreover, the major type of potential BrC in HULIS and MP carbon fractions are oxidized BBOA, but the potential BrC chromophores in LP are mainly associated with primary BBOA. This study reveals that biomass burning has adverse effects on radiative forcing and air quality, and probably indicates the significant influences of atmospheric oxidation reactions on the forms of chromophores.